North African migration systems: evolution, transformations and development linkages - de Haas, H (International Migration Institute, 2007)
The main aim of this paper is to understand the evolution and transformation of North African migration systems since 1945 within a conceptual framework drawing on migration systems and transitional migration theory. The analysis shows how regional migration dynamics have been an integral part of more general political and economic transformations. While the core Maghreb countries (Morocco, Algeria, Tunisia) have become firmly integrated into the Euro-Mediterranean migration system, Egypt has been predominantly connected to the Gulf (GCC) migration system. Intra-regional migration has mainly been focused on Libya. Recently, regional migration systems show increasing complexity and interconnectivity, while increasing migration from sub-Saharan Africa towards Libya and other North African countries might herald their future transition into settlement countries. The extent to which policies can enhance the development impact of migration is assessed by focusing on Morocco. Recent increases in remittances and (holiday) returns suggest that Morocco’s policies towards migration and development have been successful at least to a certain extent. However, the analysis also exemplifies that specific “diaspora policies” have only limited effects if they are not accompanied by structural political and economic reform.